2018
DOI: 10.3390/diseases6030079
|View full text |Cite
|
Sign up to set email alerts
|

“Holes” in the Jaw—A Report of Two Cases of Periapical Actinomycosis

Abstract: Periapical actinomycosis is a relatively rare form of cervicofacial actinomycosis, which typically involves the periapical region with subsequent potential spread to the jaw bones. We hereby present two cases of periapical actinomycosis. Both patients presented with jaw pain and “holes” in their gum and lacked the characteristic clinical features commonly seen in cervicofacial actinomycosis such as jaw mass, draining ulcers, sinuses and fistulae. The first patient was an immunocompetent host with chronic stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The patient was treated with high-dose penicillin for 4 weeks and made a complete recovery [22]. Ayoade et al reported two distinct cases of periapical actinomycosis, which is a very rare presentation of the cervicofacial form [12]: both of these patients had no history of dental procedures but presented with underlying immunosuppression (due to type 2 diabetes and multiple myeloma, respectively) and they were over 60 years of age. In both cases, the diagnosis was based on histopathological examination using hematoxylin and eosin and Gomori-Grocott methenamine silver stains, where both the bacteria and the sulfur granules were shown [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The patient was treated with high-dose penicillin for 4 weeks and made a complete recovery [22]. Ayoade et al reported two distinct cases of periapical actinomycosis, which is a very rare presentation of the cervicofacial form [12]: both of these patients had no history of dental procedures but presented with underlying immunosuppression (due to type 2 diabetes and multiple myeloma, respectively) and they were over 60 years of age. In both cases, the diagnosis was based on histopathological examination using hematoxylin and eosin and Gomori-Grocott methenamine silver stains, where both the bacteria and the sulfur granules were shown [12].…”
Section: Discussionmentioning
confidence: 99%
“…Ayoade et al reported two distinct cases of periapical actinomycosis, which is a very rare presentation of the cervicofacial form [12]: both of these patients had no history of dental procedures but presented with underlying immunosuppression (due to type 2 diabetes and multiple myeloma, respectively) and they were over 60 years of age. In both cases, the diagnosis was based on histopathological examination using hematoxylin and eosin and Gomori-Grocott methenamine silver stains, where both the bacteria and the sulfur granules were shown [12]. In the case series presented by Moghimi et al [23], 19 cases of cervicofacial actinomycosis cases were characterized: all patients complained of swelling, while 17 also had severe pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actinomycosis is diagnosed by jaw bone histopathology, which showed characteristic sulfur granules and embedded actinomyces‐like organisms. The patients have excellent clinical response to 6 months of penicillin therapy without any need for surgical intervention, as is reported in literature …”
Section: Discussionmentioning
confidence: 99%
“…The patients have excellent clinical response to 6 months of penicillin therapy without any need for surgical intervention, as is reported in literature. 12 Any unidentified mass, facial swelling, or persistent infection particularly after endodontic therapy or tooth extraction, regardless of its nontraumatic history is suggestive of actinomycosis. 13 Diagnosis should be actively attempted in all instances of persistent oral infections because progressive actinomycosis, particularly in the maxilla, is likely to have relatively serious consequences if it is not diagnosed.…”
Section: Discussionmentioning
confidence: 99%